Boosting the Performance of Culinary MSMEs Through Marketing, Product Innovation, and Word of Mouth: Empirical Evidence in Jepara Regency - Rizka Cahya Rahma Dhani; Heni Susilowati (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Amidst fierce business competition, MSME operators are required to offer added value and enhance their business competitiveness. This study aims to analyse the role of packaging, product innovation and word-of-mouth in improving the business performance of MSME operators in Jepara Regency. A quantitative approach was employed using an associative research design. Questionnaires were distributed to MSME operators using purposive sampling to collect data from 100 respondents. The data were then analysed using multiple linear regression to test the relationships between the variables. The results indicate that, both partially and simultaneously, the variables of packaging, product innovation and word-of-mouth have a positive and significant effect on the business performance of SMEs in Jepara Regency. Product innovation is the most dominant factor in driving the growth of the culinary sector in Jepara. The Adjusted R-squared coefficient was 0.619, indicating that these three variables account for 61,9% of the variation in SME business performance, whilst the remainder is influenced by factors outside the scope of this study. These findings suggest that strategies focusing on packaging development, product innovation, and strengthening word-of-mouth communication are crucial factors in enhancing the success of culinary SMEs in Jepara Regency amidst an ever-evolving market landscape.